THE PURSUIT OF SELF-ESTEEM IN PHYLLIS WHITNEY’S NOVEL “HUNTER’S GREEN” - Siskawati, Zulfia (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2020)
Abstract This study analyses Phyllis Whitney’s novel “Hunter’s Green”. The problem of this study is to what extend the novel reveal the pursuit of Self-Esteem and how the elements of novel; character and setting support the pursuit of self -esteem. The result of the study shows that there are three features of pursuit of self-esteem conducted by the character Nigel Barrow. They are building awareness, getting support, and gaining position. Building awareness is revealed through the condition of Nigel, as low class person, lives in high-class family, Athmore, which is full of superiority. He realizes his positive value; superior in brain and has the same chance to enter the school just like the high class does. Gaining support is revealed through the condition in which Nigel lives among people who judge him low. He proves himself to get support from his society. Gaining position is by having position as educated and privileged person through attaining prestigious school. He attains the school by winning himself a difficult scholarship. It gives sense of satisfaction and pride on himself since his condition born as low class. Nigel also gets position as wealthy person through doing precious business in the field of building and real estate in Bahamas. This is part of Nigel’s pursuit of self-esteem since Nigel gets it in competitive condition. This condition enriches his view on himself as worthy person who has potentials and capabilities. Hopefully, there must be something to learn in the literary work in spite of its mere function as entertainment. Kata Kunci: pursuit, self-esteem Abstrak Studi ini adalah analisa novel Phyllis Whitney Hunter’s Green. Permasalahan yang dibahas dalam analisa ini adalah sejauh mana novel ini memperlihatkan pengejaran harga diri (The Pursuit of Self-Esteem) dan bagaimana elemen-elemen novel yang difokuskan kepada character (tokoh) dan setting (latar) mendukung pengejaran harga diri tersebut. Tujuan dari analisa ini adalah untuk mendapatkan jawaban sejauh mana novel Hunter’s Green memperlihatkan pengejaran self-esteem dan bagaimana elemen setting dan character mendukung pengejaran self-esteem dalam novel ini. Dari penganalisaaan didapatkan bahwa tokoh Nigel Barrow, yang berasal dari status rendah melakukan berbagai usaha untuk mengejar harga dirinya. Usahanya itu adalah dengan membangun kesadaran akan potensi dirinya dan keberhargaan dirinya (building awareness) dengan meraih dukungan dari lingkungan (gaining support) dan dengan meraih posisi ditengah-tengah masyarakatnya (gaining position). Usaha-usaha yang dilakukan Nigel ini adalah bahagian dari pengejaran harga diri karena dia merasa puas dan bangga akan kemampuannya dalam kondisi kompetitif. Keyword: pursuit and self-esteem